Treatment and prophylaxis of NSAID-induced gastropathies in a therapeutist’s practice - T. L. Lapina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review – to present up-to-date data on application of proton pump inhibitors (PPI) e.g. esomeprazole for treatment and prophylaxes of gastropathies, induced by intake of nonsteroid anti-inflammatory drugs (NSAIDs).Original positions. PPI serve as drugs for treatment and prophylaxis of NSAIDs-induced gastropathies. Recently carried out controlled studies showed clinical efficacy of esomeprazole in conducting patients with NSAID -gastropathies. The drug in a dose of 20 and 40 mg is significantly faster and resulted in healing of stomach ulcer at higher number of patients in comparison to ranitidine in a dose of 300 mg for 8 wks of treatment. Esomeprazole (20 and 40 mg) appeared effective for prophylaxis of erosions and ulcers at long-term intake of NSAID and-or aspirin in placebo- controlled investigations. Dyspepsia which was not related to erosiveulcerative lesions of upper regions of gastro-intestinal tract (GIT), was successfully stopped by prescription of esomeprazole in the same dose to the 4-th week of treatment, and the maintaining course for 6 months promoted the relapse of pain and epigastric discomfort on a background of ongoing intake of NSAID.Conclusion. Esomeprazole can be utilized at whole spectrum of undesirable effects of NSAID and aspirin on the upper regions of GIT both for treatment and prevention.